The ν4 bands at 11 µm: linelists for the Trans- and Cis- conformer forms of nitrous acid (HONO) in the 2019 version of the GEISA database. (18th August 2022) - Armante, R.; Perrin, A.; Kwabia Tchana, F.; Manceron, L.
Abstract : Using parameters of line positions and line intensities existing in the literature for the Trans- and Cis- conformer forms of nitrous acid (HONO), we generated, for the first time, a linelist of positions, intensities, and line shape parameters for the ν4 bands of nitrous acid located at 790.117 and 851.943 cm −1 for the Trans- and Cis- conformers, respectively. A validation of this linelist was performed using spectra recorded by the IASI (Interféromètre Atmosphérique de Sondage Infrarouge) satellite instrument in February 2009 during the (rather) exceptional conditions of the large Australian bush fires. This list, which is now included in the 2020 version of the GEISA database (https://geisa.aeris-data.fr/ ), is of potential interest for the IASI-NG (Infrared Atmospheric Sounding Interferometer – New Generation) instrument which will be launched on board the METOP-SG satellite in 2021. GRAPHICAL ABSTRACT: UF0001